A Comparison of Push-Out Bond Strength of Two Endodontic Sealers to Root Canal Dentin: An in Vitro Study - Adl A; Sobhnamayan F; Sadat Shojaee N; Azizi Sh (Shiraz University of Medical Sciences, 2016)
Statement of Problem: Adhesion to root canal dentin is one of the necessary characteristics of endodontic sealers. MTA Fillapex (Angelus, Londria, PR, Brazil) is one of the recently introduced MTA-based sealer. Only a limited number of studies have evaluated the bonding of this sealer to the dentin, with conflicting results. Objectives: The purpose of this study was to evaluate the bond strength of MTA Fillapex sealer) to root canal dentin compared to an epoxy resinbased sealer (AH26 sealer). Materials and Methods: Twenty root blocks (6mm length) were acquired from the middle part of the extracted single-rooted central or lateral maxillary incisor roots and their lumens were enlarged to achieve a diameter of 1.3 mm. MTA Fillapex and AH26 were placed in the lumens of root blocks (n = 10). The specimens were kept in an incubator for 7 days, the roots were sectioned perpendicular to their long axis to achieve slices with thickness of 1 mm and the push-out test was carried out by a universal testing machine. Results: The mean value of bond strength was 1.84 ± 0.7 Mpa for AH26 and 0.19 ± 0.1 Mpa for MTA Fillapex. The difference between the two groups was statistically significant (p < 0.001). Conclusions: With in the limitation of this study, AH 26 showed significantly higher bond strength in comparison to MTA Fillapex.